The history of the birth of the secular Islamic state of Turkey and the idea of the renewal of Mustafa Kemal Ataturk - Hannanong, Ismail; Murniati, Murniati; Hasaruddin, Hasaruddin; Syukur, Syamzan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This article discusses the history of the birth of the secular Islamic State of Turkey and the ideas of reform carried out by Mustafa Kemal Ataturk in various fields and its transformation into a modern, secular state. The method used in this research is a literature review using a qualitative approach. The analysis used to analyze the data is content analysis. The research results show that Mustafa Kemal Ataturk was one of the qualified Islamic reformers of the 19th century. He has made a major contribution to changing the mindset of Turkish society. By changing the old order that had become a tradition in the Ottoman Empire, and forming it into a new face with a style of thinking that actually did not change "Islam" but only changed the mindset and order of life of Muslims to adapt to the demands of the times. Islamic values were formed, a caliphate, a republic and even a secular one. Even though symbols are also important, what is more important is that the people are able to convey the substance of Islam in every movement of their people's lives. His ideas have brought Turkey to become a developed country that is on par with the international world as well as proving that Islamic government is a government that is in line with the demands of the times.